Prevalence of female sexual dysfunction and its associated factors among type 2 diabetes mellitus patients In Kuantan, Pahang - Md Aris, Mohd Aznan; Tan, Kui Foung; Mohd Rus, Razman (2021)
Introduction: Diabetes mellitus is associated with various complications, including sexual dysfunction. The objectives of this study were to measure the prevalence of female sexual dysfunction (FSD) and its associated factors among type 2 diabetes mellitus (T2DM) patients attending primary health clinics in Kuantan. Materials and Methods: A cross-sectional study was conducted in 5 primary care clinics in Kuantan. Data were collected using an interviewer-administered questionnaire. The Questionnaire is divided into 3 sections: sociodemographic, Malay Version of Female Sexual Function Index (MVFSFI), and 9-item patient health questionnaire (PHQ-9). Data were analysed using SPSS version 25.0. Results: This study had recruited 241 respondents. The mean age of respondents involved was 52.9 (7.75). The majority were Malay (79.3%), Muslim (80.5%), housewives (68%), and menopause (54.4%). The prevalence of FSD was 39.8%. The most common sexual dysfunction was desire (63.5%), followed by arousal (44.4%), lubrication (35.7%), orgasm (38.6%), satisfaction (38.6%) and pain (33.6%). Multivariate analysis showed that non-Malay (AOR: 2.5, 95% CI:1.24 to 5.23), depression (AOR: 4.5, CI:1.30 to 15.57), and longer duration of marriage (AOR 1.08, CI:1.03 to 1.14) were significantly associated with FSD while having more children is a protective factor (AOR: 0.82, CI:0.69 to 0.97). Conclusion: Prevalence of FSD was high and clinicians should concern sexual health as an essential aspect to be focused on when treating T2DM patients, especially among non-Malay, patients with a longer duration of the marriage, a lesser number of children, and those who presented with depressive symptoms